Microsoft Outlook 2000 e-mail and fax guide - Mosher, Sue (Digital Press, 2000)
Microsoft Outlook 2000 E-mail and Fax Guide teaches advanced users and administrators, especially those within networked organizations using Exchange Server, how to manage and optimize Microsoft Outlook, the industry's leading messaging client, and use it as an effective tool for organizational communications. Written by one of the industry's leading experts on Outlook, Microsoft MVP-recognition winner Sue Mosher, the book concentrates on features, techniques and troubleshooting vital to advanced users and administrators but which are covered lightly, if at all, by other books on Outlook. Rather than offering only basic instruction or, like mammoth tomes on the topic, surveying every Outlook feature for every conceivable Outlook user, administrator, and developer, Microsoft Outlook 2000 E-mail and Fax Guide provides extensive instruction and best practices on the Outlook e-mail, fax and workgroup capabilities considered critical by sophisticated and frequent users of Outlook.